2011
DOI: 10.1056/nejmsa1008268
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Public-Sector Research in the Discovery of Drugs and Vaccines

Abstract: Public-sector research has had a more immediate effect on improving public health than was previously realized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
126
0
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(140 citation statements)
references
References 7 publications
4
126
0
10
Order By: Relevance
“…The centrality of academic centers and public funding in pharmaceutical development has been noted in other studies. 27 However, it is frequently challenged by those who argue that research within companies is the main source of innovative drug products. 3,28,29 This claim has been used to justify high prescription drug prices, especially in the United States, to support the continuing supply of innovative products.…”
Section: Discussionmentioning
confidence: 99%
“…The centrality of academic centers and public funding in pharmaceutical development has been noted in other studies. 27 However, it is frequently challenged by those who argue that research within companies is the main source of innovative drug products. 3,28,29 This claim has been used to justify high prescription drug prices, especially in the United States, to support the continuing supply of innovative products.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, one recent study found that publicly funded research formed the foundation for almost all the newuse FDA approvals that were examined. 6 Going forward, the public sector's role is likely to increase -the new National Center for Advancing Translational Sciences at the National Institutes of Health has explicitly embraced the search for new uses in a number of the programs it is funding.…”
Section: T He Drug Price Competitionmentioning
confidence: 99%
“…The research conducted by Zycher et al shows also that, public research institutions have contributed to the discovery of 9,3% to 21,2% of all drugs involved in new-drugs applications approved during the period from 1990-2007. These proportions are higher than those identified before [21]. The examined data also suggest that public research institutions in USA tend to discover drugs that are expected to have a disproportionately important clinical effect.…”
Section: Basic Research In Use -New Growth Areasmentioning
confidence: 78%
“…Zycher et al [21] found that at least 80% of 35 major drugs were based on scientific discoveries made by public institutions. Toole found a quantifiable correlation between investment in publicly funded basic research and corporately funded applied research: 1% increase in the funding in public basic research led to increase of 1,8% in the number of successful applications for new molecular entities in the lag of 17 years.…”
Section: Basic Research In Use -New Growth Areasmentioning
confidence: 99%